Tandem Mass: The Creation and Appropriation of a Liquid Chromatography - Smruti Ranjan Dash; Mahendra Kumar Sahu (International Journal of Medical Toxicology and Legal Medicine, 2024)
The remarkable method for chemical and pharmaceutical analysis that can separate, analyse, and/or purify any material is liquid chromatography. For the purpose of separating drug particles and performing their metabolite bioanalysis, a variety of analytical techniques are employed, including mass spectrometry (MS), capillary electrophoresis (CE), gas chromatography (GC), radioimmunoassay (RIA), fluorescence, and refractive index. The most popular ones are chromatography-based. The ability of chromatography to separate materials and mass spectrometry (MS) has completely changed the way chemical analysis is conducted today. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) equipment is highly versatile and selective. Because of its outstanding selectivity, high sensitivity, and rapid analysis, LC-MS/MS is a commonly used and ideal method for evaluating medicines and their metabolites. Even at lower concentrations, analytes that are easily separated by liquid chromatography can be identified by MS/MS detection due to a variety of ionisation techniques, including electro-spray ionisation (ESI), atmospheric pressure photo ionisation (APPI), and air pressure chemical ionisation (APCI). A fingerprint mass spectrum is produced by MS and includes information on the molecular weight and fragmentation ions peculiar to a given structure. The primary flaw of MS is its inability to handle compound mixes. Tandem mass spectrometry (MS/MS) can assist with this problem to some extent. Therefore, when HPLC and MS are interfaced, the very sensitive and structure-specific detection capabilities of MS and the high-resolution separation skills of HPLC benefit each other. MS functions as an all-purpose LC detector nearly flawlessly.